Progression of asymptomatic mild carotid artery stenosis: Implications for frequency of surveillance. (October 2017) - Hamilton, Russell D; Shield, Cory E; Laughrun, David
We looked retrospectively at the 3- to 5-year progression of mild, asymptomatic carotid artery stenosis (CAS). A random sample of 600 patients who had undergone at least two carotid artery duplex ultrasounds between 31 October 2006 and 1 November 2016 with a second duplex ⩾3 and ⩽5 years following the initial one were screened for inclusion. Internal carotid arteries (ICAs) were included if they had 20–49% stenosis on the initial duplex, with 440 carotid arteries meeting this criteria. Analyses were performed utilizing chi-squared and two-tailed t- tests. Twenty-four (5.45%) of the initial 440 carotid arteries progressed to moderate CAS. There was a statistically significant increase in the prevalence of hypertension (68% vs 47%, p= 0.022) and diabetes mellitus (44% vs 22%, p =0.008) in patients with carotids that progressed to moderate CAS. There was a decrease in moderate-intensity statin use (32% vs 58%, p =0.005) and an increase in patients not on statins (36% vs 11%, p =0.001) in the group of carotids that progressed to moderate CAS. One carotid artery (0.2%) progressed from mild CAS to severe CAS. If supported by others, our data may lead to a change in the recommendations regarding appropriate follow-up of asymptomatic CAS.